1984
DOI: 10.1159/000194628
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Bronchospasmolytic Effect of Fenoterol (0.2 mg) and Salbutamol (0.4 mg) as Powder inhalations in 20 Patients with Reversible Bronchial Obstruction

Abstract: In a double-blind crossover study, the effects of fenoterol powder inhaled from capsules (0.2 mg) and the powder inhaler with salbutamol capsules (0.4 mg) were compared. A single dose of each was administered on 2 subsequent days in random order. The effects on lung function test results were followed from 15 to 360 min after administration. Apart from the overall comparison, special attention was paid to the beginning and the end of the test periods. Statistically significant differences were found only in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The rationale of this investigation is based on former experiences with fenoterol inhalation powder, which, just as ipratropium inhalation powder, also consists of glucose powder. Several studies have demonstrated that fenoterol inhalation powder (200 ng) is equipotent to the same dose inhaled from the fenoterol pressure aerosol (1,6,8,9).…”
mentioning
confidence: 99%
“…The rationale of this investigation is based on former experiences with fenoterol inhalation powder, which, just as ipratropium inhalation powder, also consists of glucose powder. Several studies have demonstrated that fenoterol inhalation powder (200 ng) is equipotent to the same dose inhaled from the fenoterol pressure aerosol (1,6,8,9).…”
mentioning
confidence: 99%